The Relationship Between Knowledge and Attitudes towards the Incidence of Anemia in Adolescent Girls at YM Vocational School in 2024 - Syahrul Rudiansyah; Sulfiah, Wili; Anggraini, Lita; Ningsih, Selviana; Nurmaulina, Nasya (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2025)
Anemia can cause various adverse effects for adolescent girls and wus (women of childbearing age = 15-49 years), including a weakened immune system, making patients more susceptible to infection, reduced physical and thinking abilities due to insufficient oxygen supply to the muscles and brain, and decreased academic achievement and work efficiency. This study aims to reveal various influences related to the occurrence of anemia in grade X and XI female students at SMK "YM" in 2024. The study used a correlative descriptive study with a cross-sectional design. Data from direct observation from 195 respondents through sampling and terminology analysis using a chi-square statistical approach. The results of the chi-square statistical approach showed that there was no significant relationship between knowledge (p value 0.078) and attitude (p value 0.276) with the association of anemia in female students in grades X and XI at SMK "YM" in 2024. The results of the analysis found that two variables were associated with the occurrence of low hemoglobin levels in students in grades X and XI at SMK "YM" in 2024.